Molecular analysis of PALB2‐associated breast cancers. Issue 1 (30th March 2018) - Lee, Jue Er Amanda; Li, Na; Rowley, Simone M; Cheasley, Dane; Zethoven, Magnus; McInerny, Simone; Gorringe, Kylie L; James, Paul A; Campbell, Ian G
Abstract: PALB2 is established as the most clinically important moderate to high penetrance breast cancer predisposition gene after BRCA1 and BRCA2 . Mutations in classical familial cancer predisposition genes are presumed to be recessive at the cellular level and therefore a second inactivating somatic mutation is required in the tumour tissue. However, from the limited data that exist, PALB2 may be an example of a cancer predisposition gene that does not conform to Knudson's 'two hit' paradigm. We conducted genome‐wide copy number analysis and targeted sequencing of PALB2 and other breast cancer driver genes in 15 invasive breast cancers from individuals carrying pathogenic germline mutations in PALB2 . The majority of cancers showed clear evidence of bi‐allelic inactivation of PALB2 (10/15) either as loss of heterozygosity involving the wild‐type allele (six tumours) or as somatic point mutations (four tumours). All PALB2 ‐null cancers had high homologous recombination deficiency (HRD) scores consistent with a homologous recombination repair deficiency. Interestingly, all but one of the PALB2 heterozygous cancers also had high HRD scores, suggesting that alternative mechanisms of PALB2 functional loss might be operating in these cancers. Our findings demonstrate that PALB2 does undergo bi‐allelic inactivation in the majority of breast cancers from PALB2 germline mutation carriers. This feature has implications for the discovery of new moderate to high penetrance breast cancer predisposition genes as it supports using the existence of a 'second hit' and mutation signatures as important search criteria. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.